Comprehensive Approach of Highly Resorbed Mandibular Ridge with Complete Denture - Rahmat, Alfian; Permatasari, Nina; Jubhari, Eri Hendra (Indonesia Prosthodontic Association, 2021)
Patient’s chief complaint: A 66-year-old female patient referred to the Hasanuddin University Dental Hospital with a fractured lower denture that impaired patient’s chewing ability. Patient’s oral status: Complete edentulous in maxilla and mandible with flat mandibular ridge. Clinical examination showed absence of inflammation and flabby tissues also absence of bone prominences. Treatment plan: Complete denture fabrication with semi-adjustable articulator and modification in impression technique to produce retentive denture. Details of the therapy: Preliminary impression and fabrication of anatomic cast followed by bolder molding and physiological impression. Two Dots method was used to determine the maxillomandibular relation and measure vertical dimension. Position of the maxilla was transferred using facebow which attached to the centric tray followed by mounting the cast on semi-adjustable articulator with guidance from centric tray. Artificial teeth were arranged in lingualized occlusal scheme on waxpattern and try-in was done. After processing denture, remounting and selective grinding were done including finishing and polishing, followed by insertion of denture. Summary: Impression technique is one of primary factors in management of flat mandibular ridge to utilize surrounding tissues to have both active and passive retention in dentures.